Transforming growth factor-beta and suppression of humoral immune responses in HIV infection. - Kekow, J (1991)
We reported previously that PBMC from HIV+ patients spontaneously release increased levels of TGF beta 1, contributing to defects in cellular immune responses. This study defines the implications of TGF beta overexpression for humoral immunity in HIV infection. We found that upon Staphylococcus aureus Cowan I (SAC) stimulation of cells from HIV+ donors, B-lymphocyte proliferative responses were decreased. This deficiency correlated closely (r = 0.7, P less than 0.001) with increased TGF beta secretion by PBMC from HIV-infected donors. Conditioned medium from HIV+ PBMC and purified TGF beta 1 had similar inhibitory effects on SAC- or EBV-induced B-cell proliferation, and B cells from HIV-infected donors were as sensitive to inhibition by TGF beta as cells from normal donors. Antibodies to TGF beta 1 neutralized the inhibitory effect of HIV+ culture supernatants on normal B cells and increased low proliferative responses by HIV+ cells. Using PWM as stimulus for B cell differentiation, it was shown that activated TGF beta from HIV+ PBMC is able to significantly reduce the induction of immunoglobulins and this effect was also abrogated by anti-TGF beta. These studies support the concept that in HIV infection, TGF beta is a potent suppressor, not only of the cellular, but of the humoral immune responses as well.